The expression and clinical prognostic value of protein phosphatase 1 catalytic subunit beta in pancreatic cancer. Issue 1 (1st January 2021) - Hu, Lingyu; Xu, Haokai; Wang, Xiaoguang; Wu, Bin; Chen, Fei; Chen, Wei; Gao, Yong; Zhong, Zhengxiang
ABSTRACT: Pancreatic cancer (PAAD) is a common malignancy with a poor survival rate. The identification of novel biomarkers could improve clinical outcomes for patients with PAAD. Here we evaluated the expression and clinical significance of PPP1CB in PAAD. PPP1CB expression was higher in PAAD tissue than in matched paracancerous tissue ( P < 0.05 ). We predicted a network of regulatory targets and protein interaction partners of PPP1CB, and identified a PPI network consisting of 39 node genes. The expression of 33 node genes was higher in PAAD tissue than in matching paracancerous tissue. High expression of the node genes ACTN4, ANLN, CLTB, IQGAP1, SPTAN1, and TMOD3 was associated with improved overall survival ( P < 0.05 ). SiRNA knockdown of PPP1CB significantly reduced the migration and invasion of PAAD cells. A PPP1CB immunohistochemical staining was performed using a tissue microarray (TMA), consisting of tumor samples collected from 91 patients with PAAD (88 of which contained matched paracancerous tissues). The expression of PPP1CB in PAAD was significantly higher than in the matched paracancerous tissue, ( P = 0.016 ). High PPP1CB expression was associated with patient sex ( P = 0.048 ), alcohol use ( P = 0.039 ), CEA ( P= 0.038 ), N stage ( P = 0.001 ), and invasion of nerve ( P = 0.036 ). Furthermore, high PPP1CB expression was associated with significantly poorer overall survival ( P = 0.022 ). Our data demonstrate that PPP1CB is associated with the migration and invasion of PAAD cells, and may be useful as an independent prognostic indicator for clinical outcome in patients with PAAD. Graphical abstract: uf0001